The The Aspects that Affect Verbal Communication in Intercultural Communications - Abasenga, Albert (Journal of History Culture and Art Research, 2023)
Globally, people passed and raised in different environments, cultural backgrounds, situations, and circumstances. These several backgrounds can affect their communications in one way to another when they are transmitting, addressing, sending, sharing and receiving different perspectives, thoughts, guidance, advice or opinions from others. For that, the present study aims to discuss the aspects of verbal communication that facilitate and impede intercultural communication between human beings. The aspects that the study is discussing are related to speaking skills and writing skills including voice, the diction of words, and phraseology. This article uses critical analysis and fact data from both society and the written documents of scholars, for giving and addressing clear outcomes. The study advises that people should be aware of their counterparts' cultural backgrounds in order to facilitate their communications effectively. It also advises the communicators to make some research about the culture of their counterparts and train themselves about other’s languages and their usage.